Web-based bim project execution plan management system (WeB-MaS) for public works department Malaysia - Tsai, Kai Len (2022)
The effective uses of Building Information Modelling (BIM) Project Execution Plan (BPEP) are one of the success factors for a successful BIM implementation. However, a preliminary study with JKR indicated current BPEP preparation and management is inefficient and time-consuming due to the manual data entry. Furthermore, data inconsistency occurs due to the inability for real-time BPEP collaboration and updates as well as lack of BPEP document management. Hence, this research aims to develop a webbased BPEP Management System (WeB-MaS) for the case study research; JKR by improving the efficiency of BPEP preparation and management. The research’s first objective which is to examine the user requirements of JKR for the development of WeBMaS was conducted through a semi-structured interview with JKR BIM Unit. Consequently, to develop WeB-MaS as the second objective, Agile Scrum methodology was adopted. The last objective, which is to evaluate the user acceptance, usability, and advantage of WeB-MaS was fulfilled by conducting a questionnaire evaluation with JKR BIM Unit. WeB-MaS was designed according to JKR BPEP template with real-time element, ability to be in synced with mobile application, and accompanied with verification and review features. WeB-MaS received optimistic reviews by the JKR BIM unit and the system will be handed over to JKR. In regard to the concern on WeB-MaS security, future improvements will be made by migrating the WeB-MaS to JKR internal server. In conclusion, WeB-MaS ensures the quality of BIM information through BIM collaboration to improve productivity and efficacy of the BPEP preparation and management process.